Diabetes mellitus and the risk of multidrug resistant tuberculosis: a meta-analysis - Qianqian Liu (Nature Portfolio, 2017)
Abstract The high prevalence of diabetes mellitus (DM) among multidrug resistant tuberculosis (MDR-TB) patients is a serious cause for concern. We conducted a meta-analysis to determine whether DM is an independent risk factor for MDR-TB. Electronic literature searches of the PubMed, Web of Science and EMBASE databases up to July 12, 2016 were conducted. The pooled adjusted odds ratio (OR) and 95% confidence intervals (CIs) were calculated using the random effects model with STATA 12.0 software. In total 13 studies, including 9289 individuals with TB, were included in this meta-analysis. Significant association between DM and MDR-TB (OR = 1.71; 95% CI = 1.32, 2.22) was identified. Subgroup analyses showed that: 1) Pooled OR was 1.25 (95% CI: 0.82–1.91) for cross-sectional studies, and was 2.14 (95% CI: 1.51–3.02) for longitudinal studies; 2) The pooled OR was 1.69 (95% CI:1.09–2.62) for primary MDR-TB, 1.94 (95% CI:1.42–2.65) for any MDR-TB, and 0.85 for secondary MDR-TB (95% CI: 0.29–2.54); 3) DM was significantly associated with MDR-TB in both Caucasian (OR = 2.26, 95% CI: 1.66–3.07) and Asian (OR = 1.40, 95% CI: 1.01–1.95) subgroups. No evidence of publication bias was identified. In conclusion, the pooling analysis indicated that DM was an independent risk factor for MDR-TB, especially for primary MDR-TB.